Phases, Methods, and Approaches to Developing Students’ Reading Skills in English - Soliyev Umidjon Yulchivoyevich (Indonesian Journal Publisher, 2025)
This article addresses the methodological issues of developing reading competence in English language lessons. It presents a detailed analysis of the stages, forms, and means of teaching reading in English classes. It is argued that teaching based on authentic texts proves to be an effective approach. However, it is also noted that the development of reading competence in English language instruction has not been sufficiently studied. The article highlights current research findings and results related to the use of authentic texts in English language education. This work is particularly useful for foreign language teachers and students specializing in foreign languages, especially in preparing their graduation qualification papers